Der kartellrechtliche Marktbegriff und unentgeltliche Leistungen - Vocke, Julius Conrad (Mohr Siebeck, 2021)
How is the definition of the word market interpreted in German and European antitrust law? Julius Conrad Vocke develops a market definition and, based on examples from various sectors, studies which gratuitous performance relationships can be qualified as a market in accordance with this definition. In conclusion, he deals with the special requirements of the definition of gratuitous markets.
PublicationDate: 20210317
Keywords: Common Market -- Marktabgrenzung -- Plattformen -- Marktdefinition -- Wettbewerbsparameter -- Theorie der zwei- oder mehrseitigen Märkte -- Steuererklärung -- Besonderes Verwaltungsrecht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Europarecht -- Ausländisches Recht, Rechtsvergleichung